The Financial Performance of Islamic Rural Bank in Indonesia: A Bibliometric Analysis - Wenda Wahyu Christiyanto; Ikin Solikin; Budi Supriatono Purnomo; Denny Andriana (Shirkah: Journal of Economics and Business, 2023)
No bibliometric investigation has been carried out regarding the Financial Performance of the Islamic Rural Bank in Indonesia, even though Indonesia harbors the largest Muslim population, denoting an untapped market for Islamic financial institutions. This study aims to conduct extensive bibliometric literature on Financial Performance of the Islamic Rural Bank in Indonesia. The study utilized Publish or Perish (PoP) software to identify articles related to the topic from the Google Scholar database. Out of 982 articles found between 2015 and 2020, 68 articles were relevant and selected for analysis. These articles were further processed using Mendeley reference manager software and visualized using VOSviewer. The study outcomes provide a comprehensive view of the timeframe of publications, academic journals, citation rates, authorship, research subjects, and methodologies applied in examining financial performance. It provides a summary of the variables that impact the financial performance of Islamic rural banks in Indonesia and puts forth an all-encompassing framework for predicting the financial performance of these banks. This study serves as a valuable reference for future research on the Financial Performance of Islamic Rural Banks in Indonesia by providing an overview of potential topics, research methodology, variables involved, and a suggested financial performance model for Islamic rural banks in Indonesia.